LANGUAGE ACQUISITION STRATEGY INVENTORY FOR AUTONOMOUS LEARNERS: DISPLAYING STUDENTS' ACADEMIC WRITING SKILLS THROUGH BLENDED LEARNING [INVENTARIS STRATEGI PEMBELAJARAN BAHASA UNTUK PEMBELAJAR MANDIRI: MENUNJUKKAN KEMAMPUAN MENULIS AKADEMIK SISWA MELALUI PEMBELAJARAN BLENDED] - Audi Yundayani; Hanna Sundari; Fiki Alghadari (Universitas Pelita Harapan, 2026)
The pedagogical implementation of blended learning, which advances students' autonomous learning and mastery, shapes academic writing performance in higher education. Nevertheless, more study is needed to examine how autonomous learning and language acquisition strategies affect college students' academic writing products in blended learning settings. The current study examines the academic writing performance of students in language learning and autonomous learning strategies they employed through blended learning. This is a mixed-method research design which twenty-seven students in higher education participated in this study. They were evaluated using questionnaires on autonomous learning and strategy inventory language learning and writing tests. The study found that the academic writing scores of the participants ranged from 50.5 to 96, which was indicative of low autonomy. A range of 51 to 94.5 scores suggests that learners are highly autonomous. In addition, 39.51% of participants preferred memory strategies, 14.81% preferred compensatory strategies, and 2.47% preferred cognitive strategies. In the study, 11.11% of participants implemented affective strategies, 4.94% employed social strategies, and 27.16% employed metacognitive strategies. Moreover, the study found the preferred strategies employed by participants to develop their academic writing skills through varying engagement and retention strategies related to language knowledge, which, in turn, influence their academic writing performance. It is essential to take these preferences into account when creating a language learning strategy inventory for English academic writing courses in higher education, as this will foster autonomous learning. Additionally, the development of engaging blended learning activities is expected to enhance students’ academic writing skills. Abstrak Bahasa Indonesia Implementasi pedagogis pembelajaran campuran, yang mendorong pembelajaran mandiri dan kemampuan mahasiswa, memengaruhi kinerja penulisan akademik di perguruan tinggi. Namun, diperlukan penelitian lebih lanjut untuk mengkaji bagaimana pembelajaran mandiri dan strategi akuisisi bahasa memengaruhi produk penulisan akademik mahasiswa dalam lingkungan pembelajaran campuran. Penelitian ini mengkaji kinerja penulisan akademik mahasiswa dalam pembelajaran bahasa dan strategi pembelajaran mandiri yang mereka terapkan melalui pembelajaran campuran. Metode penelitian campuran dilakukan dengan melibatkan 27 mahasiswa dengan menggunakan kuesioner tentang pembelajaran mandiri, inventaris strategi pembelajaran bahasa, dan tes menulis. Temuan penelitian menunjukkan bahwa peserta umumnya menunjukkan tingkat otonomi belajar yang rendah dalam proses penulisan artikel akademik mereka. Selain itu, ditemukan preferensi yang bervariasi terhadap strategi pembelajaran bahasa, dengan kecenderungan yang jelas terhadap penggunaan strategi berbasis memori dibandingkan dengan strategi kognitif, sosial, atau afektif. Pola ini menunjukkan bahwa peserta lebih mengandalkan strategi yang melibatkan retensi informasi daripada strategi yang mendorong interaksi, refleksi, atau regulasi emosional dalam proses penulisan. Selain itu, penelitian ini menemukan strategi yang disukai oleh peserta dalam mengembangkan keterampilan menulis akademik mereka melalui berbagai strategi keterlibatan dan retensi yang berkaitan dengan pengetahuan bahasa, yang pada gilirannya mempengaruhi kinerja menulis akademik mereka. Penting untuk mempertimbangkan preferensi belajar mahasiswa saat mengembangkan rencana pembelajaran menulis akademik bahasa Inggris di perguruan tinggi, karena hal ini akan mendorong pembelajaran mandiri. Selain itu, pengembangan aktivitas pembelajaran campuran yang menarik diharapkan dapat meningkatkan keterampilan menulis akademik mahasiswa.